Anatomy of xylem and phloem in stems and roots of Populus sibirica and Ulmus pumila from semi-arid steppe in Mongolia - Anastazija Dimitrova; Angela Balzano; Katarina Čufar; Gabriella S. Scippa; Maks Merela; Antonio Montagnoli; Batkhuu Nyam-Osor; Enkhchimeg Tsedensodnom Chimgee; Donato Chiatante (Les)
The present study focuses on the cambium and the anatomy of secondary tissues (xylem – wood and phloem) of Siberian poplar (Populus sibirica) and Siberian elm (Ulmus pumila) grown in a plantation in the semi-arid Mongolian steppe. Stem and root microcores from both species were collected and subsequently processed to obtain cross-sections for light microscopy by paraffin embedding, sectioning with a rotary microtome, and staining with safranin and astra blue. The results present the anatomy of the secondary xylem and phloem of stems and roots of both species, along with the characteristics of the youngest xylem and phloem annual rings. We discuss the critical aspects which need to be considered when using the microcoring methodology, along with the need for further studies on wood and phloem formation of less-commonly studied tree species and their characteristics when grown in semi-arid environments.